Layout influence on microwave performance of graphene field effect transistors. Issue 16 (1st August 2018) - Giambra, M.A.; Benfante, A.; Zeiss, L.; Pernice, R.; Miseikis, V.; Pernice, W.H.P.; Jang, M.H.; Ahn, J.‐H.; Cino, A.C.; Stivala, S.; Calandra, E.; Busacca, A.C.; et al.
Abstract : The authors report on an in‐depth statistical and parametrical investigation on the microwave performance of graphene FETs on sapphire substrate. The devices differ for the gate‐drain/source distance and for the gate length, having kept instead the gate width constant. Microwave S ‐parameters have been measured for the different devices. Their results demonstrate that the cut‐off frequency does not monotonically increase with the scaling of the device geometry and that it exists an optimal region in the gate‐drain/source and gate‐length space which maximises the microwave performance.